Deletion of Glutamine Synthetase Gene Disrupts the Survivability and Infectivity of Leishmania donovani - Kumar, Vinay; Ghosh, Sanhita; Roy, Kamalika; Pal, Chiranjib; Singh, Sushma (Frontiers in Cellular and Infection Microbiology, 2021)
Glutamine synthetase (GS) is one of the most important metabolic enzymes which catalyzes ligation of glutamate and ammonia to form glutamine. Previous studies from our lab had revealed significant differences in parasite and host GS enzyme which warranted us to further work on its relevance in parasite. To analyze glutamine synthetase function in Leishmania, we generated GS overexpressors and knockout mutants and evaluated their ability to grow in vitro in monocyte differentiated macrophage and in vivo by infections in BALB/c mice. GS knocked out strain showed significant growth retardation with delayed cell cycle progression and morphological alteration. Null mutants exhibited attenuated infectivity both in in vitro and in vivo experiments and the effect was reverted back when infected with GS complemented parasites. This indicated that the alterations in phenotype observed were indeed due to GS knockout. GS knockout also made the parasite increasingly sensitive to Miltefosine. Detailed investigation of mode of parasite death upon Miltefosine treatment by dual staining with Annexin-V conjugated FITC and propidium iodide, pointed towards apoptotic or necrotic mode of cell death. This is the first report to confirm that GS is essential for the survivability and infectivity of Leishmania donovani, and can be exploited as a potential drug-target.